Family-Based Diabetes Self Management Education (DSME) Terhadap Self Care Pasien Dengan Luka Ulkus Diabetikum - Andi Chrismilasari, Lucia; Jamini, Theresia; Kusuma Negara, Candra; Machelia Champaca, Septi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Diabetes mellitus (DM) is a chronic disease with an increasing prevalence and often leads to serious complications such as diabetic foot ulcers. In Indonesia, this complication frequently occurs due to patients’ poor self-care abilities, particularly in foot care and blood glucose monitoring, which increases the risk of amputation. Diabetes Self-Management Education (DSME) is an educational approach aimed at improving patients’ knowledge and skills in managing their condition independently. This study aimed to evaluate the effectiveness of DSME interventions in enhancing self-care among DM patients with diabetic foot ulcers. A quasi-experimental design with a one-group pre-test and post-test approach was used. A total of 30 respondents participated in a seven-day DSME intervention that included face-to-face education sessions on foot care, glucose monitoring, dietary management, physical activity, and medication adherence. Self-care ability was measured before and after the intervention using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Data were analyzed using paired sample t-tests. The results showed a significant increase in self-care scores from a mean of 17.9 ± 3.4 at pre-test to 22.6 ± 3.1 at post-test (p < 0.001). These findings indicate that the DSME intervention is effective in improving patients’ self-care abilities. It is recommended as a standard educational strategy in healthcare facilities to prevent complications and improve diabetic wound management.